Telaah Kritis Terhadap Pandangan Roh-Roh Teritorial Menurut C. Peter Wagner - Toni Irawan (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2020)
AbstractThis paper intends to criticize he views on territorial spirits developed by C. Peter Wagner. In his hypothesis he argued